Analysis of research methodology on the content of heavy metals in sediments on the Indonesian coastal - Sayed Abdul Azis; Muhammad Irham; Sugianto Sugianto; Ichsan Setiawan; Amri Adnan (Depik, 2021)
Heavy metal pollution is one of the problems that often occurs in Indonesian coastal waters. Comparative methods of looking at heavy metal content in coastal sediments include a way to show similarities and differences between one or more articles by using certain criteria. Different comparison methods to see the heavy metal content in sediments include the AAS (Atomic Absorption Spectrophotometer) method, AAN (Netron Activation Analysis), Regression, and USEPA methods. Based on the comparison of 2 methods, namely: AAS and AAN methods, the most efficient in analyzing heavy metals in sediments in coastal areas is the Atomic Absorption Spectrophotometry (AAS) method compared to the Neutron Activation Analysis (AAS) method.Keywords:CoastalSedimentHeavy MetalSpectrophotometer